Water Quality Modeling of Dubai Creek using HEC-RAS - Hussien, Heba (2015)
A Master of Science thesis in Civil Engineering by Heba Hussien entitled, "Water Quality Modeling of Dubai Creek using HEC-RAS," submitted in May 2015. Thesis advisor is Dr. Maruf Mortula and thesis co-advisor is Dr. Serter Atabay. Soft and hard copy available.